2018
DOI: 10.1371/journal.pone.0206685
|View full text |Cite
|
Sign up to set email alerts
|

The combination of aldehyde dehydrogenase 1 (ALDH1) and CD44 is associated with poor outcomes in endometrial cancer

Abstract: Aldehyde dehydrogenase 1 (ALDH1) and CD44 have been established as biomarkers for predicting the survival of many types of cancer patients. This study evaluated the expression and clinical significance of these putative cancer-cell markers in a series of tumor samples from endometrial cancer (EC) patients using tissue microarray. We examined 245 endometrial samples, including 132 (53.87%) pre-malignancy lesions and 113 (46.12%) malignant endometrial lesions from biopsies or hysterectomies. We examined the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Moreover, a fraction of ALDH1A1-expressed cells was higher in clinical specimens from advanced-stage or high-grade cancer than from earlystage or low-grade cancer (Figure 5C). Kaplan-Meier survival analyses of 35 patients with advanced-stage cancer showed that high ALDH1A1 expression was correlated with survival rate (Figure 5D, p < 0.01 for progression-free survival; Figure 5E, p = 0.015 for overall survival), consistent with previous reports (Huang et al, 2018;Rahadiani et al, 2011). Univariate and multivariate analyses revealed that positive ALDH1A1 staining was an independent prognostic factor of both progression-free and overall survival in patients with advanced-stage endometrial cancer (legend continued on next page)…”
Section: Aldh1a1 Expression Is Correlated With Poor Prognosis In Patients With Endometrial Cancersupporting
confidence: 91%
“…Moreover, a fraction of ALDH1A1-expressed cells was higher in clinical specimens from advanced-stage or high-grade cancer than from earlystage or low-grade cancer (Figure 5C). Kaplan-Meier survival analyses of 35 patients with advanced-stage cancer showed that high ALDH1A1 expression was correlated with survival rate (Figure 5D, p < 0.01 for progression-free survival; Figure 5E, p = 0.015 for overall survival), consistent with previous reports (Huang et al, 2018;Rahadiani et al, 2011). Univariate and multivariate analyses revealed that positive ALDH1A1 staining was an independent prognostic factor of both progression-free and overall survival in patients with advanced-stage endometrial cancer (legend continued on next page)…”
Section: Aldh1a1 Expression Is Correlated With Poor Prognosis In Patients With Endometrial Cancersupporting
confidence: 91%
“…CD44 can be a promising candidate for predicting the prognosis of cancer patients [85,[127][128][129][130][131][132]. Based on immunohistochemistry analysis of 125 breast cancer patient samples, it was found that CD44 protein level was positively correlated with poor disease-free survival (DFS) and OS [133].…”
Section: Cd44 and Prognosis Of Cancer Patientsmentioning
confidence: 99%
“…High expression of CD44 alone predicts poor overall survival, and simultaneous expression of CD44 and Aldehyde dehydrogenase 1 is linked to extremely unfavorable overall survival among endometrial cancer patients [130].…”
Section: Cd44 and Prognosis Of Cancer Patientsmentioning
confidence: 99%
“…In patients with uterine endometrioid carcinosarcoma, high ALDH1 expression predicted poor prognosis, lymphatic invasion, recurrence, and low overall survival [73]. ALDH high CSCs cells have distinct stem-like properties, such as high expression of stem-cell markers BMI1, HEY1, HES1, and adhesive molecule CD44 [41,74,75]; in addition, reduced expression of differentiation markers, enhanced migration, high tumorigenicity, and self-renewal ability were reported [76]. When EC cells were sorted using flow cytometry and cultured in vitro, ALDH high cells yielded both ALDH high and ALDH low cells, whereas ALDH low cells only yielded ALDH low cells [72].…”
Section: Aldh and Uterine Cancermentioning
confidence: 99%
“…Clinically, high ALDH expression is associated with poor outcomes in several gynecologic malignancies, including ovarian cancer (OC) [17,[37][38][39][40], endometrial [41], and cervical cancer (CC) [42,43], as well as other solid tumors including breast [44][45][46], lung adenocarcinoma [47], rectal [48], esophageal squamous adenocarcinoma [49], gastric [50], colorectal [51], prostate [52], and neuroblastoma [53]. To our knowledge, there are no published reports correlating ALDH and prognosis in vulvar or vaginal cancer.…”
Section: Introductionmentioning
confidence: 99%